Bananapants ebook A bonkers romantic comedy. - Reid, Penny (Cipher-Naught, 2024)
Estranged childhood friends unexpectedly reunite under bizarre circumstances and bicker their way to love in this bonkers romantic comedy. Ava Archer misses her best childhood friend most especially during the month of April. Ask any tax attorney, it's a lonely, grueling time of year. Luckily, Ava has just received a surprising and delectably absurd offer from her posh doppelgänger at work. She must pretend to be the aforementioned posh co-worker for one night at an extremely fancy party; a party so fancy, there exists absolutely no chance anyone will recognize her or suspect her ruse. . . Desmond (Des) Sullivan is a thief. And not the heart-of-gold kind. He's the steal-from-the-rich-and-give-to-the-also-rich-so-he-can-get-paid kind. He does, however, have one firm rule: never steal what the target can't afford to lose. After a brutal falling out with his father, Desmond hasn't returned to Chicago in over ten years. But when a good friend is swindled and something priceless is stolen, Desmond must return home, both as himself and his thieving alter ego. Infiltrate a dangerous secret society of the world's most elite billionaires while leveraging his estranged father's resources and not blowing his cover? Sure. No problem. Or it wouldn't be a problem if Ava Archer hadn't just walked into the room, wearing a ridiculous wig, speaking with a preposterous accent, and pretending (badly) to be someone she's not. Bananapants is a full-length, contemporary romantic comedy filled with hijinks and shenanigans. It can be read as a standalone, but the parents of the main characters will be familiar to anyone who has read the Knitting in the City series.